Neuropathy among drug resistant HIV Patients treated in Jakarta - Ibnu A Ariyanto; Fitri Octaviana; Churi Wardah; Ekawati Beti; Silvia Widyaningtyas; Budiman Bela; Patricia Price; Amin Soebandrio (Journal of Infection in Developing Countries)
Introduction: Some people living with HIV (PLWH) receiving ART in Indonesia display poor clearance of replicating virus. This has been associated with HIV-associated sensory neuropathy. Here we assess whether treatment failure reflects the presence of drug resistance mutations.